Pengaruh Keterampilan, Pengalaman Kerja, dan Komitmen Kerja terhadap Kinerja Karyawan pada CV Medali Mas - Seno Rahmad Kartiko; Brahma Wahyu; Erwin Syahputra (Jurnal Manajemen Bisnis Digital Terkini, 2025)
A company's productivity is greatly influenced by the quality of employee performance, which makes employees an important asset in achieving organizational goals. This study aims to analyze the influence of job skills, work experience, and work commitment on employee performance on CV Medali Mas. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected through questionnaires that had been tested for validity and reliability, and classical assumption tests were carried out including normality, multicollinearity, heteroscedasticity, and linearity tests. The results of the analysis showed that simultaneously, the three independent variables, namely work skills, work experience, and work commitment, had a significant effect on employee performance (F count = 6.788; Sig. < 0.001). However, only work experience showed a significant effect on employee performance (t count = 2.765; Sig. = 0.009), while work skills (Sig. = 0.072) and work commitment (Sig. = 0.531) had no significant effect. These findings confirm that work experience is a dominant factor in improving employee performance at CV Medali Mas. The implications of this study suggest that companies pay more attention to the track record of work experience in the recruitment and human resource development process to increase productivity optimally.